Sejarah Multikulturalisme dan Moderasi Beragama - Agustina, Helda; Purnamasari, Imelda Anggi; Yasin, Muhammad (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI Sangatta Kab. Kutai Timur., 2025)
Multiculturalism is a view that recognizes and appreciates cultural, ethnic and religious diversity in society. In Indonesia, multiculturalism develops along with social dynamics, colonialism, migration, and globalization. Religious moderation is a strategic approach in maintaining a balance between the implementation of religious teachings and the principles of tolerance and social harmony. This research aims to examine the historical development of multiculturalism and the role of religious moderation in shaping the socio-cultural character of Indonesia's pluralistic society. The formulation of the problem includes how multiculturalism was formed since the time of kingdoms such as Sriwijaya and Majapahit and how the value of religious moderation is internalized in people's lives. The method used is a literature study with analysis of scientific sources including academic books, scientific journal articles, and historical documents. This study shows that these values have been inherent since the early days of civilization, through inclusive religious practices, the role of religious leaders, and traditional educational institutions, which collectively form a tolerant and harmonious society.